Analisis Pengaruh Kemudahan, Kegunaan dan Tingkat Resiko Terhadap Keputusan Masyarakat Sukoharjo Menggunakan Shopeepay - Mufti Arief Arfiansyah; Defi Vebriani; Afifatul Makarim (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
In today's digital era, information progress is spreading fast and getting more advanced. Technology transfer can control various elements of people's habits that impact daily activities. The use of social media by mobile phones is increasing every year. The annual increase causes various innovations, one of which is financial technology or fintech. An example of fintech that is often used today is the Shopeepay e-wallet. The purpose of this analysis is to understand the impact of convenience, usability & risk on the certainty of using Shopeepay in the Sukoharjo Regency area. This form of study uses prime data. How to take samples with cluster random sampling. The total sample is 100 respondents by providing an online questionnaire in the form of a G-Form. Multiple linear regression with SPSS 23 is used for data processing. Simultaneous research on usage decisions. It is known that the results of the research that the researchers conducted were that perceived convenience had no significant impact on the decision to use shopeepay, then perceived usefulness had an effect on using shopeepay, and perceived risk had an effect on decisions on using shopeepay in the community in Sukoharjo. The results of the validity test are declared valid, and the reliability test is declared reliable